ANALISIS KONTRAK IJARAH - Kurniawan, Puji (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2018)
Humans are social creatures who need each other to socialize or to fulfill their needs, such as primary, secondary and tertiary needs. In this life there are 2 (two) groups of people, namely groups of people who are overfunded and those who are underfunded. Therefore, banks and non-bank financial institutions have emerged as intermediaries between the 2 (two) groups of the people so that the balance can occur in meeting the needs of each life. In Indonesia, there are many conventional and sharia bank and non-bank financial institutions that provide financing services to meet human needs. The fundamental difference between conventional and Islamic financial institutions is the use of the interest system which is usury in conventional financial institutions and the use of profit sharing systems in Islamic financial institutions.